Kandungan Total Bakteri dan Total Fungi pada Pellet Limbah Penetasan yang Dibuat dengan Penambahan Bentonit - Aprilian Adi Nugroho; Sri Sumarsih; Bambang Sulistiyanto (Agricultural Faculty, 2016)
ABSTRAK. Penelitian efek penambahan bentonit dalam proses pelleting terhadap total bakteri dan total fungi dari produk pellet limbah penetasan sebagai bahan pakan alternatif, telah dilaksanakan di Laboratorium Teknologi Pakan, Fakultas Peternakan dan Pertanian, Universitas Diponegoro. Penambahan bentonit pada proses pelleting diharapkan mengurangi total bakteri dan total fungi pada pellet olahan limbah penetasan, sehingga aman digunakan sebagai bahan pakan alternatif. Pada penelitian ini limbah penetasan yang berupa cangkang telur, telur infertile, telur gagal menetas, serta DOC afkir dan mati dihancurkan, dicampur dengan bentonit dan dibuat pellet, untuk kemudian dianalisis kandungan total bakteri dan total fungi pada produk pellet. Perlakuan bentonit dilakukan dengan aras 0, 2, 4 dan 6% (B/B). Penelitian dilakukan dengan rancangan acak lengkap (RAL) 4 perlakuan dan 5 ulangan. Data dianalisis dengan analisis ragam dan dilanjutkan dengan uji wilayah ganda Duncan untuk mengetahui perbedaan antar perlakuan. Hasil menunjukkan bahwa pemberian bentonit dari berbagai level berpengaruh sangat nyata (P0,01). Pemberian bentonit pada tingkat tertinggi (6%) mampu menekan total bakteri dan total fungi pada kisaran 105 cfu/g. Disimpulkan bahwa bentonit mampu menekan kandungan total bakteri dan total fungi pada produk pellet limbah penetasan.(Numbers of total bacteria and total fungi of hatchery waste pellets that made by adding bentonite)ABSTRACT. A Research about the effect of bentonite addition in the pelletizing process on total bacteria and total fungi of pellet product of hatchery waste as an alternative feedstuff, was done at Feed Technology Laboratory, Faculty of Animal and Agricultural Sciences, Diponegoro University. The addition of bentonite was expected to reduce the number of bacteria and fungi in the pellet product of hatchery waste, therefore, it could be used safely as an alternative feedstuff. In this experiment, the hatchery waste in the forms of eggshell, infertile eggs, un-hatched eggs, dead and culled DOC were blended, mixed with bentonite and pelleted,and then the number of total bacteria and total fungi of pellet was analyzed. The treatment was carried out with the level of bentonite i.e. 0, 2, 4 and 6% (w/w). Completely randomized design (CRD)was applied by 4 treatments and 5 replications of each. Data analyzed by analysis of variance (ANOVA), and followed by Duncan multiple range test (DMRT) to determine differences among the treatments. The results showed that administration of bentonite at various levels significantly affect the number of bacteria and fungi in the hatchery waste pellets (P 0.01). Administration of bentonite at the level of 6% shows the highest value on suppressing the content of total bacteria as well as fungi up to the range of total content 105cfu/g. In conclusion, the bentonite was able to suppress the total amount of bacteria and total fungi in the hatchery waste pellets.